Development and thinking of Broadband Beijing construction - Hua JIN; Zhaohan LI; Hui CHEN (Dianxin kexue)
The Ministry of Industry and Information Technology (MIIT) organized series of investigation activities around the subject of “‘Broadband China' strategy implementation”in 2016,aiming at promoting“Broadband China”construction as well as summing up good experience and typical practice.Based on the research of broadband network construction progress in Beijing,the achievements of broadband network construction in Beijing in recent years were reviewed.Secondly,the successful practice and excellent experience in the implementation of“Broadband China”was summarized.The existed difficulties on broadband networks promoting were analyzed and some suggestions and solutions were put forward.